Classicism, Christianity and Ciceronian academic scepticism from Locke to Hume, c.1660-c.1760 - Stuart-Buttle, T (2013)
This study explores the rediscovery and development of a tradition of Ciceronian academic scepticism in British philosophy between c.1660-c.1760. It considers this tradition alongside two others, recently recovered by scholars, which were recognised by contemporaries to offer opposing visions of man, God and the origins of society: the Augustinian-Epicurean, and the neo-Stoic. It presents John Locke, Conyers Middleton and David Hume as the leading figures in the revival of the tradition of academic scepticism. It considers their works in relation to those of Anthony Ashley Cooper, third earl of Shaftesbury, and Bernard Mandeville, whose writings refashioned respectively the neo-Stoic and Augustinian-Epicurean traditions in influential ways. These five individuals explicitly identified themselves with these late Hellenistic philosophical traditions, and sought to contest and redefine conventional estimations of their meaning and significance. This thesis recovers this debate, which illuminates our understanding of the development of the ‘science of man’ in Britain. Cicero was a central figure in Locke’s attempt to explain, against Hobbes, the origins of society and moral consensus independent of political authority. Locke was a theorist of societies, religious and civil. He provided a naturalistic explanation of moral motivation and sociability which, drawing heavily from Cicero, emphasised the importance of men’s concern for the opinions of others. Locke set this within a Christian divine teleology. It was Locke’s theologically-grounded treatment of moral obligation, and his attack on Stoic moral philosophy, that led to Shaftesbury’s attempt to vindicate Stoicism. This was met by Mandeville’s profoundly Epicurean response. The consequences of the neo-Epicurean and neo-Stoic traditions for Christianity were explored by Middleton, who argued that only academic scepticism was consistent with Christian belief. Hume explored the relationship between morality and religion with continual reference to Cicero. He did so, in contrast to Locke or Middleton, to banish entirely moral theology from philosophy.